Serum microRNAs in clear cell carcinoma of the ovary - Angel Chao; Chyong-Huey Lai; Hua-Chien Chen; Chiao-Yun Lin; Chia-Lung Tsai; Yun-Hsin Tang; Huei-Jean Huang; Chen-Tao Lin; Min-Yu Chen; Kuang-Gen Huang; Hung-Hsueh Chou; Ting-Chang Chang; et al. (Taiwanese Journal of Obstetrics & Gynecology, 2014)
Objective: To identify candidate microRNAs (miRNAs) in the serum of patients with clear cell carcinomas in monitoring disease progression. Materials and methods: The sera of patients with diagnosed ovarian clear cell carcinoma were collected from 2009 to 2012. Real-time quantitative polymerase chain reaction (PCR) analysis for 270 miRNAs was performed. To offset the potential extraction bias, an equal amount of Caenorhabditis elegans cel-miR-238 was added to each serum specimen before miRNA isolation. miRNA expression was analyzed using the ΔCt method, with cel-miR-238 as controls. Results: Twenty-one patients with clear cell carcinoma were included. In the discovery phase on four pairs of pre- and postoperative sera, 18 differentially expressed miRNAs were selected from 270 miRNAs. In the validation phase on an independent set of 11 pairs of pre- and postoperative sera, 4 miRNAs (hsa-miR-130a, hsa-miR-138, hsa-miR-187, and hsa-miR-202) were confirmed to be higher in the preoperative sera. In the application phase, hsa-miR-130a remained consistent with the different time points in seven of the 10 patients during clinical follow-up periods. More importantly, in three patients, hsa-miR-130a levels were elevated in early disease recurrences before CA125 was found to be elevated. Conclusion: Hsa-miR-130a may be a useful serum biomarker for detecting recurrence of ovarian clear cell cancer, and warrants further studies.